Designing Production Lines And Producing Fish Nuggets In The Crunchy Nugget Business - Dessy Aliandrina; Devy Cathrine (ConCEPt - Conference on Community Engagement Project, 2023)
The purpose of this study was to determine the condition of "Crunchy Nuggets" from the aspect of production management. This research was conducted from September to December 2022, and data were analyzed using qualitative descriptive analysis. The concept of this business is to sell fish-based nuggets, This business development includes marketing, operational and financial planning. The marketing plan includes promotion using social media. The operational plan includes purchasing raw materials, producing nuggets, and distributing products to consumers directly. The findings show that Crunchy Nugget has provided benefits, but still faces several problems, such as sudden engine damage, non-standard products and difficulty finding ingredients.